Bifurcation Theory with Applications (IntechOpen, 2024)
Bifurcation Theory with Applications is a collection of chapters that describe the theory and application of nonlinear dynamics to a wide variety of problems in physics and engineering. Each chapter is self-contained and includes an introduction, main contributions, and details of up-to-date theoretical, computational, and experimental results. The book examines various practical systems, including models of target detection in cells through the analysis of bio-nanomachine, attractant, and repellent concentrations. It addresses the quasistatic evolution of anelastic structures, explores the generation of triangular patterns through anisotropic diffusion, and discusses the stabilization of time-delay distributed bilinear systems in spatial domains. Topics also include optimal control challenges in bilinear systems with unbounded and bounded control sets, forward bifurcation in hepatitis B virus infection models, and the bifurcation of hematological stem cells with feedback control in a biological context. The book is designed for theorists, applied mathematicians, and engineers across diverse scientific disciplines, serving as a valuable resource for anyone interested in bifurcation theory’s wide-ranging applications.